KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI TERMINAL TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN SIKKA TAHUN 2014-2018 - Yulista, Maria Renilda; Penu, Yustina Paulina; Sagajoka, Estherlina (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
This study discusses the Contribution of Regional Taxes and Terminal Levies on the Regional Original Income of Sikka Regency during 2014-2018, with the aim of the research is to find out 1) the magnitude of the contribution of regional taxes and terminal levies to the Regional Original Income (PAD) of Sikka Regency, 2). the level of effectiveness of local taxes and terminal levies on regional revenue in Sikka Regency. The type of research used is descriptive quantitative research, which is calculating the data obtained to solve existing problems in accordance with the research objectives. The data analysis technique used is descriptive quantitative, namely calculating the amount of contribution, and the effectiveness of local taxes and district terminal fees. Sikka 2014-2018. The results of this study indicate that the contribution of regional tax revenues to the Regional Original Revenue of Sikka Regency in 2014 to 2018 does not make a significant contribution to the PAD of Sikka Regency because the criteria for regional tax contributions are 10% -20%, the Contribution of Terminal Levies Receipts on PAD of Sikka Regency in 2014-2018 it was very lacking in making a meaningful contribution to PAD in Sikka Regency because the criteria for the contribution of terminal fees only reached 0.00% -10%. The average criteria for the effectiveness of local tax revenues in Sikka Regency during 2014-2018 were less effective because the criteria were 60% -80%, the average criteria for the effectiveness of receiving terminal fees in Sikka Regency during 2014-2018 were not effective because the criteria were less than 60 %. The lack of contribution of local taxes and terminal levies to PAD in Sikka Regency is due to the lack of public awareness of the obligation to pay taxes, lack of facilities and infrastructure for tax collection officers, levies are not running well, users of terminal services are less aware of paying fees, as well as the level of discipline and the officers' sense of responsibility is very lacking.